Trying to build a classless utopia in the land of racial democracy: the lack of racial discussion within the educational materials of the Brazilian Landless Rural Workers' Movement. Issue 2 (4th March 2017) - Straubhaar, Rolf
Abstract: The hegemonic ideology of racial democracy and rural cultural norms of racial silence continue to inform racial identities and national racial discourse in Brazil, in this case within the Landless Rural Workers' Movement (MST), a left-wing movement for agrarian reform. In this article I engage in textual analysis of a textbook from the MST's youth curriculum, arguing that the language used in this textbook does not recognize the centrality of race in world or Brazilian history, but rather focuses on the role of social class in marginalization. I also argue that race is largely ignored in the textbook's description of the MST itself, despite the organization working in rural areas that are predominantly indigenous or Afro-descendant. Lastly, I argue that language is used which implicitly separates the MST leadership from indigenous and Afro-Brazilian populations. The implications of these findings are analyzed through the lens of critical race theory and Brazilian rurality.